Penyelenggaran Kegiatan Pengabdian Kepada Masyarakat; Diskusi Budaya Kaum Muda Dengan Tema Menuju Kebudayaan Lombok Utara yang Berkelanjutan - Putra, Sandi; Mandini, Denda Devi Sarah; Audina, Pin Kharisma; Zulhadi, Zulhadi; Rusyada, Gozin Najah (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2025)
Local culture is a collective identity that is an important foundation for development based on local wisdom. However, the flow of globalization and modernization has caused the erosion of cultural values, especially among the younger generation. This community service activity aims to increase awareness and active participation of the younger generation in preserving local culture in North Lombok Regency. The method used was holding a cultural discussion forum which was held on February 11, 2025 in the Hall of the North Lombok Regent's Office, involving 100 participants from youth elements, policy makers, cultural figures, and the arts community. The results of the activity showed high enthusiasm and active involvement of youth in the discussion, as well as the emergence of a number of strategic recommendations, such as the integration of cultural values ????in the education curriculum, strengthening the role of women and indigenous communities, and utilizing digital technology for cultural promotion. The conclusion of this activity shows that cross-sector and generation forums are able to encourage the formation of a sustainable cultural ecosystem, adaptive to developments in the times, but still based on local values ????that are the main strength of the North Lombok community.